Crack-free conjugated PbS quantum dot-hole transport layers for solar cells - Sharma, Ashish; Dambhare, V. Neha; Bera, Jayanta; Sahu, Satyajit; Rath, Arup K. (ACS Applied Nano Materials, 2021)
Colloidal quantum dots (QDs) benefit from solution-phase processing and band-gap tuning for their application in solar cell development. Today's QD solar cells rely on solid-state ligand exchange (SLE) to replace bulky oleic acid (OA) ligands with small 1,2-ethanedithiol (EDT) ligands to develop a conducting hole transport layer (HTL). High volume contraction in EDT conjugated QD films, however, leads to crack and porosity in the HTL, which is a major cause of concern for the device reproducibility and large-area solar cell development. We show that partial removal of the OA ligands in the solution phase reduces the volume contraction in solid films, thereby allowing the growth of crack-free QD films in the SLE process. The cleaning of QDs by repeated precipitation and redispersion using a protic methanol (MeOH) solvent helps with partial removal of the OA ligands, but it is detrimental to the electronic properties of QDs. We develop a one-step solution-phase partial ligand-exchange process using ammonium salts, which enable partial replacement of the OA ligands and passivation of the QD surface. Introduction of the facile partial ligand-exchange process eliminates the need for tedious and wasteful multiple cleaning steps with MeOH, while improving the photophysical properties of QDs. The advancement in QD processing helps to build crack-free, smooth, and conjugated QD films for their deployment as HTLs in solar cell development. Partial ligand exchange with NH4SCN leads to a 1.5 times increase in p doping and mobility over multiple MeOH-cleaned PbS QD films. HTLs developed using NH4SCN QDs show an improved photovoltaic performance to attain a 10.5% power conversion efficiency. Improvement in the depletion width and hole collection efficiency leads to a superior photovoltaic performance, as confirmed from experimental studies and one-dimensional solar cell capacitance simulation.
Keywords: Efficiency; ligand; polydispersity; quantum dot; solar cells; thin film

Reduction of hydroxyl traps and improved coupling for efficient and stable quantum dot solar cells - Mandal, Debranjan; Dambhare, V. Neha; Rath, Arup K. (ACS Applied Materials & Interfaces, 2021)
Progress in quantum dot (QD)-based solar cells has been underpinned by the improvements in surface passivation and advancements in device engineering. Acute control over the surface properties is crucial to restrict the formation of in-gap trap states and improve the QD coupling in achieving conducting QD films. In this report, we demonstrate a solution-phase hybrid passivation strategy, which is beneficial in removing detrimental hydroxyl traps and improving the coupling between QDs by reducing the interdot distance. Advancement in surface passivation is translated to the long carrier lifetime, higher carrier mobility, and superior protection toward degradations in QD solids. The performance of solar cell devices is increased by 26% to reach an efficiency of 10.6%, compared to the state-of-the-art lead halide passivated solar cells. The improvement in solar cell performance is supported by the reduction of trap states and an 80 nm increase in thickness of the light-absorbing QD layer.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation

Thiocyanate- and thiol-functionalized p-doped quantum dot colloids for the development of bulk homojunction solar cells - Dambhare, V. Neha; Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (Energy Technology, 2022)
Progress in device engineering and surface passivation strategies has led to steady progress in colloidal quantum dot (QD) solar cells. Bulk homojunction (BHJ) device architecture has several advantages over the conventional planar junction in developing QD solar cells. Herein, surface ligand chemistry is utilized to control the doping type and dispersibility of oppositely doped PbS QDs to develop BHJ solar cells. Thiocyanate and thiol ligand combination is introduced to develop p-PbS QD ink, which is blended with halide-passivated n-PbS QDs to build BHJ solar cells. It is shown that BHJ solar cells are benefited from high energy offset and higher hole mobility. This leads to the superior carrier extraction from a thicker active layer without compromising fill factor and open circuit voltage. Power conversion efficiency has reached 10.7% in 530 nm-thick BHJ solar cells, a 24% improvement over the best performing planar solar cells. With the help of the 1D solar cell capacitance simulator, it is shown that a 15% efficient QD solar cell can be realized by further improving the hole mobility above 0.1 cm(2) V-1 s(-1).
Keywords: bulk homojunctions; Doping; quantum dots; solar cells; surface functionalization

Solution-phase ligand engineering for all-quantum-dot near-infrared light-emitting diodes - Biswas, Arindam; Mitra, Anurag; Sharma, Ashish; Shinde, Dipak Dattatray; Dambhare, V. Neha; Sharma, Anjali; Mahajan, Chandan; Rath, Arup K. (ACS Applied Nano Materials, 2024)
Strong emission over a wide near-infrared (NIR) region makes lead sulfide quantum dots (QDs) a preferred material in building NIR light-emitting diodes (NIR-LEDs) for numerous applications. Narrow-bandgap emitter QDs blended in the matrix of high-band gap QDs offer a simple yet powerful architectural platform for building high-performance NIR-LEDs. So far, the all-QD-based blend architecture has been realized using a poorly controlled solid-state ligand exchange approach. Advanced solution-phase ligand exchange, which offers greater control over surface passivation, is yet to be realized in all-QD LED device construction. We observe that the solution-phase ligand exchange from the optimized lead halide and thiol ligand combination, used in high-performing QD solar cell construction, is inefficient in realizing efficient all-QD LEDs, which could have restricted the adoption of the solution-phase ligand exchange thus far. Here, we introduce an innovative dual-ligand strategy to build all-QD-based NIR-LEDs using an advanced solution-phase ligand exchange approach. Through ligand engineering of matrix QDs, we managed to improve photoluminescence quantum yield (40%), reduce trap density (10(14) cm(-3)), and prolong carrier lifetime (832 ns). The LED devices benefit from improved electronic properties and balanced carrier injection to yield 6% EQE and 7.7% PCE, which are six times higher than those of state-of-the-art ligands.
Keywords: electroluminescence; lead sulfide; ligand passivation; light-emitting diodes; near-infrared; quantumdots